2016
DOI: 10.1007/s00248-016-0890-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon-Fixation Rates and Associated Bacterial Diversity and Abundance in Three Natural Ecosystems

Abstract: CO assimilation by autotrophic microbes is an important process in soil carbon cycling, and our understanding of the community composition of autotrophs in natural soils and their role in carbon sequestration of these soils is still limited. Here, we investigated the autotrophic C incorporation in soils from three natural ecosystems, i.e., wetland (WL), grassland (GR), and forest (FO) based on the incorporation of labeled C into the microbial biomass. Microbial assimilation of C (C-MBC) differed among the soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 57 publications
3
38
2
Order By: Relevance
“…ε values for form IC RubisCOs have yet to be determined. Form IC RubisCO gene sequences are commonly detected in samples collected from soil, lakes, rivers and estuaries (Selesi et al ., ; Tolli and King, ; Nigro and King, ; Brauer et al ., ; ; Yuan et al ., ; Wu et al ., ; Alfreider et al ., ; Lynn et al ., ) as well as the open ocean (Caspi et al ., ; Pichard et al ., ). Facultative autotrophs with form IC RubisCOs are commonly cultivated from soil, lake and river samples; these Alpha ‐ proteobacteria and Beta‐proteobacteria may be responsible for the molecular detection of form IC enzymes from these habitats (e.g., Brauer et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…ε values for form IC RubisCOs have yet to be determined. Form IC RubisCO gene sequences are commonly detected in samples collected from soil, lakes, rivers and estuaries (Selesi et al ., ; Tolli and King, ; Nigro and King, ; Brauer et al ., ; ; Yuan et al ., ; Wu et al ., ; Alfreider et al ., ; Lynn et al ., ) as well as the open ocean (Caspi et al ., ; Pichard et al ., ). Facultative autotrophs with form IC RubisCOs are commonly cultivated from soil, lake and river samples; these Alpha ‐ proteobacteria and Beta‐proteobacteria may be responsible for the molecular detection of form IC enzymes from these habitats (e.g., Brauer et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…An exact calculation of the proportion of CO2-fixing bacteria on the total bacterial community is not achievable based on functional gene abundance data. Nevertheless, supposing that (i) the average copy number of 16S rRNA copies per genome in the bacterial cells is four to six and (ii) the average number of cbb operons in bacteria is two (Yuan et al 2013;Lynn et al 2017), then we can estimate that 2-3% of the bacteria in the pond sediments may have the potential to fix CO2 through the CBB cycle.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to affecting plant physiology and growth, soil pH affects soil biogeochemistry and microbial communities (Wu et al, 2013). SEM analysis revealed that the effect of intercropping treatments on the abundance of cbbL and nosZ genes was mediated by the increase in soil pH (Lynn et al, 2017). This is in line with previous findings that plant diversity increases soil pH and microbial biomass as well as bacterial and fungal abundance (Latz et al, 2016; Wang et al, 2008; Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%